DAMPAK HUTAN TANAMAN INDUSTRI PT. WIRAKARYA SAKTI TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DESA BINAAN KECAMATAN TEBING TINGGI KABUPATEN TANJUNG JABUNG BARAT - Susliana, Susliana; Hamid, Ernawati; Yanita, Mirawati (Fakultas Pertanian, Universitas Janabadra, 2024)
This study aims to: 1) describe HTI management by PT. WKS District I, 2) analyze socio-economic conditions of assisted village communities, and 3) examine HTI management impact on community transformation and development. Using primary and secondary data with quantitative descriptive analysis, the research covered 97 respondents from Purwodadi, Delima, and Dataran Kempas villages. Results indicate well-planned HTI management creates a conducive economic climate and positive multiplier effect on community welfare. Observed socio-economic impacts include: 1) secondary education level (59.79% high school) and good health (98.97% healthy), 2) new business opportunities (20.62% entrepreneurs/traders, 41.24% permanent employees/laborers), 3) high average village income (IDR 4,462,371), and 4) correlation between education, work type, and income, with higher incomes leading to more consumptive lifestyles and health awareness.